1990
DOI: 10.1111/j.1365-2826.1990.tb00656.x
|View full text |Cite
|
Sign up to set email alerts
|

Corticotrophin‐Releasing Factor‐41 in the Human and Rat—Utility of a Highly Sensitive Enzyme Amplified Immunometric Assay

Abstract: RbstractW e have developed a highly sensitive and specific immunoassay for humanlrat corticotrophin-releasing factor-41 (CRF-41) to enable determination of immunoreactive CRF-41 levels in biological samples. To achieve high specificity, sensitivity and s p e e dwe have used two antisera in a sandwich enzyme immunoassay combined with enzyme amplification. The assay h a s a sensitivity of 0.08 fmollwell compared with radioimmunoassay sensitivities of 0.5 fmol/tube and is highly specific for the intact CRF-41 mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…In our study, we used an ultrasensitive immunometric assay which is both more sensitive and specific for rat CRF-41 than available radioimmunoassays (Milton et al, 1990a). The basal release of irCRF-41 reported for the rat hypothalamic enn I fragment system corresponded to 8.6 ± 0.8 fmol/hypothalamus per 20 min (Tsagarakis et al, 1988) and is within the range found in the present study.…”
Section: Basal Ircrf-41 and Irpge2 Releasesupporting
confidence: 82%
See 1 more Smart Citation
“…In our study, we used an ultrasensitive immunometric assay which is both more sensitive and specific for rat CRF-41 than available radioimmunoassays (Milton et al, 1990a). The basal release of irCRF-41 reported for the rat hypothalamic enn I fragment system corresponded to 8.6 ± 0.8 fmol/hypothalamus per 20 min (Tsagarakis et al, 1988) and is within the range found in the present study.…”
Section: Basal Ircrf-41 and Irpge2 Releasesupporting
confidence: 82%
“…IrCRF-41 was measured with an ultra-sensitive, highly specific enzyme amplified immunometric assay (Milton et al, 1990a) modified with a monoclonal antibody (KCHMB003) to rat CRF-41 (Milton et al, 1990b …”
Section: Rat Hypothalamus In Vitromentioning
confidence: 99%
“…Of the three 'two-site' assays reported for CRH to date, two (Linton et al 1987, Milton et al 1990) were beheved to be suitable for direct plasma measurement despite the presence of the CRH-BP. Although there was concern that the binding protein would cause interference in one of these assays, it was assumed that the IRMA antibodies then in use were of sufficiently high affinity to dissociate CRH from the CRH:CRH-BP complex, rather than measure the complex intact (Linton et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Many different CRH assays have now been described; most RIAs for plasma or serum CRH estimation require an initial extraction step to overcome plasma matrix effects and Sep-Pak C18 (Sasaki et al 1984), immunoaffinity (Suda et al 1985), vycor glass (Cunnah et al 1987) and methanol (Ellis et al 1988) have all been used for this purpose. Several two-site or sandwich immunoassays depending on the use of antibodies to distinct and non-overlapping regions of CRH have also been developed, two describing measurement in un¬ extracted samples (Linton et al 1987, Milton et al 1990), and a third which was markedly inhibited by human plasma (Hagan et al 1993). It is now known that a high-affinity binding protein (CRH-BP) for CRH exists in the human circulation and that most of the CRH in peripheral blood is present in its complexed form (Orth & Mount 1987, Linton et al 1988, Potter et al 1991.…”
Section: Introductionmentioning
confidence: 99%
“…The bioassay chosen used freshly isolated fragments of anterior pituitary in a static incubation (14,15). The two RIAs used polyclonal antisera which showed different cross-reactivities with synthetic peptide fragments (16). The two-site EAIA used two polyclonal antisera and only measured the whole molecule (16).…”
mentioning
confidence: 99%